The Strength of Organizational Culture and Education in Motivating of Entrepreneurs During the Covid-19 Pandemic - Endang Sungkawati; Ni Wayan Suarniati (Jambura Science of Management, 2022)
This study aims to determine the effect of organizational culture and education on the performance of entrepreneurs through motivation as a mediating variable. This research type is quantitative research, in terms of the level of explanation this research is associative research with a causal relationship, namely a causal relationship. This means that the research focuses on organizational culture and motivation as mediating variables. Respondents were 59 entrepreneurs and used path analysis for the analytical tool. The results of the study indicate that organizational culture, education, and motivation affect the performance of entrepreneurs, either partially or simultaneously. While motivation does not act as a mediating variable for the influence of organizational culture on performance and education on performance. Organizational culture gives a strong and appropriate influence on the performance of entrepreneurs.